ANALISIS PERKEMBANGAN PUSAT INFORMASI dan KONSELING REMAJA di SEKOLAH MENENGAH ATAS NEGERI 3 BANTUL DIY - Fujiastuti, Dwi (Universitas Ahmad Dahlan, 2019)
Introduction: Adolescence is a transitional period for an individual from childhood into adulthood, in the search of identity many teenager fall into adolescent problems such as student brawl cases that occur in major cities in Indonesia, the number of drug users in adolescents reached 14 thousand people, increased cases of smokers in the age group 16 to 19 years, increase the number of early marriage every year. PIK R aims to prepare family life for teenagers. This study aims to determine the development of the Information Center and Youth Counseling program (PIK R) so that it reaches the rigorous stage. The study was conducted at SMAN 3 Bantul, because SMAN 3 Bantul is one of the schools in the Special Region of Yogyakarta which has a PIK R called PIK R FRESS which has reached a tough stage. Method: This research is a qualitative research with descriptive research design. Research subjects were seven people who were selected by purposive sampling technique. The research was conducted by interviewing, observing, and documenting and analyzing data through the reduction, presentation and conclusion stages. Results: The step of establishing PIK R at SMAN 3 Bantul included analyzing adolescent problems, socializing students at BKKBN, socializing the formation of PIK R in the school, so that PIK R FRESS was formed. Efforts made to support the development of PIK R are activities inside and outside of school, partnership development and Human Resources. Still found adolescent problems cause of inhibiting factors included member communication, activities of PIK R, and support from the school. Conclusion: The step of establishing PIK R is in accordance with BKKBN guidelines, included analyzing until socializing programme. In development of PIK R, PIK R conducts human resource development, activities and partnerships. The inhibiting factors were support from schools and the promblem of internal PIK R.